China's currency campaign: The challenge of internationalisation and digitalisation of the renminbi - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2024)
In China, money, currency and payment transactions are manifestations of state sovereignty and political power. The primary objective of Chinese monetary policy is to maintain domestic stability, expand the scope of its own influence internationally, and reshape the global financial and monetary system to make it more compatible with the structures of the Chinese one-party state. China is pursuing the internationalisation of the renminbi on several tracks in small persistent steps and with a long-term perspective, but it has so far shied away from the decisive transition to convertibility. For the time being, the renminbi does not play a significant role on the global financial and currency markets. However, it is gaining ground as a trading, credit and reserve currency in Asia and the Global South. China is a pioneer in the development and introduction of digital central bank money. It is striving to play a leading role in the digitalisation of international payment transactions. Prospectively, the technology and infrastructure developed in China and the standards set for cross-border payments using blockchain and real-time transactions could replace the current international banking and clearing system in a cost-effective manner. The Chinese leadership believes that digital central bank money offers great potential: In terms of domestic policy, it creates further opportunities for surveillance and repression. Internationally, it would become easier for China and third countries to circumvent Western financial sanctions. In response to China's currency campaign, the European Union and the European Central Bank should step up their own efforts to internationalise and digitise the euro. Europe should avoid dependence on China when it comes to the future critical infrastructure of an interoperable system for international payments with digital central bank money.
Keywords: 320